The Influence of Soft Skill Training on Career Exploration of Guidance and Counseling Students at Ahmad Dahlan University - Danni Rosada, Ulfa; Putri Fadilah, Ananda (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
Low career exploration presents a serious challenge for students facing intense competition in the job market. This study aims to examine the influence of Soft Skill Training 1 on the level of career exploration among Guidance and Counseling (BK) students at Ahmad Dahlan University. The methodology employed is a quantitative ex post facto design with a sample of 84 students selected through training data recapitulation and the completion of a career exploration scale. The theoretical framework is based on the career exploration theory by Stumpf, Colarelli, and Hartman (1983), which views exploration as an intentional behavior to understand oneself and the work environment. Data analysis was conducted using the Spearman Rank Order test because the data were not normally distributed. The results indicate a significant positive influence between soft skill training and students’ career exploration (sig. 0.016 < 0.05) with a correlation coefficient of 0.262. The conclusion of this study confirms that intervention through RIASEC assessment-based soft skill training effectively serves as an initial stimulus for students to recognize their potential and plan their future more systematically.